Increased rate of isolation of penicillin-resistant Streptococcus pneumoniae in a children's hospital and in vitro susceptibilities to antibiotics of potential therapeutic use. - Mason, E O (1992)
The isolation of Streptococcus pneumoniae with both high and intermediate resistance to penicillin has increased in our institution since 1989 to an average of 12.1% of all isolates. We determined the susceptibilities of 95 isolates (34 susceptible to penicillin, 42 intermediate in resistance to penicillin, and 19 resistant to penicillin) to 16 antimicrobial agents of potential use in the treatment of disease caused by S. pneumoniae. Susceptibility to penicillin was determined by broth macrodilution with Mueller-Hinton broth supplemented with 5% lysed horse blood. Isolates were classified as highly resistant when the MIC was greater than or equal to 2.0 micrograms/ml, intermediate in resistance when the MIC was between 0.1 and 1.0 microgram/ml, and susceptible when the MIC was less than 0.1 microgram/ml. Fifteen of 19 isolates found to be highly resistant to penicillin were recovered from the middle ear of children. None of the isolates recovered from cerebrospinal fluid was highly resistant to penicillin. Fifteen of these isolates highly resistant to penicillin were found to be serogroup 6. Susceptibilities to other antibiotics were determined by the agar dilution method with Mueller-Hinton agar containing 5% lysed horse blood and an inoculum of 10(4) CFU per spot delivered by a replicator device. The MIC for 90% of isolates increased with increasing penicillin resistance for all antibiotics tested, except chloramphenicol, ciprofloxacin, rifampin, and vancomycin. Regardless of the classification of penicillin resistance, all isolates were classified as susceptible to cefotaxime, cefpirome, cefpodoxime, clarithromycin, imipenem, rifampin, and vancomycin on the basis of National Committee for Clinical Laboratory Standards interpretive guidelines. Interpretation of susceptibilities on the basis of currently available guidelines is difficult in that susceptibility guidelines applicable specifically to S. pneumoniae are not available.